Gastro-intestinal invasion in Hemidactylus flaviviridis with a new species of Parapharyngodon (Oxyuroidea : Pharyngodonidae) - Gupta, Neelima; Bhaskar, Manju; Gupta, Dileep Kumar (Zootaxa, 2009)
Parapharyngodon hemidactylii n. sp. (Nematoda : Oxyuridae) from the rectum of the Indian wall lizard Hemidactylus flaviviridis (n=359) is described. The parasite occurred at 79.10% (Prevalence) and 5 par/host (Mean intensity). It is compared critically with the earlier reported species based on its taxo-metric assessment. The differences in smaller size of male and female worm [male : 0.755 (0.47–0.96); female : 3.47 (2.47–4.05)], position of vulva [1.44 (1.20–1.7), tail measurements [male : 0.065 (0.01–0.09); female : 0.11 x 0.063 (0.075–0.135 x 0.045–0.10)], absence of caudal papillae and oval shaped eggs of the nematode from H. flaviviridis merits new species status.